Consolidación de un conjunto mínimo de datos para una historia clínica electrónica en atención primaria integral en salud enfocada en determinantes de la salud. - Diana Bello, Leady; Patricia Conde, Viviana; Cortés, Jennifer; Estefania Murcia, Angela; del Pilar Rincón, Andrea; Alexandra Velandia, Ariadna (Revista Salud Bosque)
Overview. The enactment of Colombian Comprehensive Health Policy and the Comprehensive Health Care Model seek a thorough understanding of risk. It is therefore necessary to implement an electronic medical record that allows for quality in health services provision, resource optimization and outcome efficacy within the Colombian healthcare system. Objective. Consolidating minimum required data set for an electronic medical record focused on primary care and health determinants. Methodology. An exploratory qualitative study was conducted and documents such as academic dissertations and handbooks produced by the Colombian Ministry of Health regarding proceedings pertaining to primary health and family health research were reviewed. A documentary analysis on the components of an electronic medical record was implemented. Further validation was conducted through data triangulation and expert advice. Results. The content of the electronic medical record is developed. Such relevant data are focused on primary care and health determinants which are the minimum required as a baseline to come up with an electronic medical record that consolidates an efficient, interoperable and user-friendly health information system. Conclusions. This documentary review reveals valuable knowledge for the implementation of integrated models of electronic medical record in primary care.